The sum of logs is the log of the product.
Law of logarithms:
![\log_b x + \log_b y = \log_b xy](https://img.qammunity.org/2019/formulas/mathematics/middle-school/1bjed2jjhuhh8a2wa4tn6fwtxf75fhk2ab.png)
Apply the law above to the left side of the equation.
![\log (x + 21) + \log x = 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/wp7aulo3l2ku89ih8r1fo5xmby5yee5lth.png)
![\log [x(x + 21)] = 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/l9dvhnqjjlooorp263q9dz8en954ubvyom.png)
![\log (x^2 + 21x) = 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ipj20xni0p3mo2vipnkcrdkjif80tdkjn0.png)
Now use the definition of log.
![\log_b x = y \Leftrightarrow b^y = x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/aw5n2h93ahr8ma8llnjdzxv47sozhg2ezy.png)
![x^2 + 21x = 10^2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3obbar00s5xcq5ezxbmdux42k4q0yrr6jh.png)
![x^2 + 21x - 100 = 0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/slm38ntbdzryrlwrtpm5nnx1p8mrjjm3bx.png)
![(x + 25)(x - 4) = 0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vjqv3bmxqobt8meot4s1b2ty7k4a6w0r7y.png)
![x + 25 = 0~~~\lor~~~x - 4 = 0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qwyqf02kf80guygjv3jinjq51qo2mezfg8.png)
![x = -21~~~\lor ~~~x = 4](https://img.qammunity.org/2019/formulas/mathematics/middle-school/56li2red8b724djhlssgd6pce1z4c0h2i6.png)
x = -21 must be discarded because log (x + 21) would become log (-21) which is not defined.
Solution: x = 4